Primary immunodeficiencies in Bulgaria - achievements and challenges of the PID National Expert Center - Naumova, Elissaveta; Lesichkova, Spaska; Milenova, Veneta; Yankova, Petya; Murdjeva, Marianna; Mihailova, Snezhina (Frontiers in Immunology, 2022)
Tremendous progress has been made in the recognition of primary immune deficiencies (PIDs) in Bulgaria since in 2005 we have joined the J Project Central-Eastern European collaborative program. Ten years later an Expert Centre (ExpC) for Rare Diseases - Primary Immune Deficiencies at the University Hospital “Alexandrovska”- Sofia was established. In May 2017 The National Register of Patients with Rare Diseases also became operational as a database containing clinical and genetic information for Bulgarian patients with PID. The transfer of data and information on Bulgarian PID patients to the European Primary Immunodeficiency Database, managed by the European Society for Primary Immunodeficiency (ESID) has started in 2020. The total number of registered patients now is 191 (100 men and 91 women), with more than half of them being children (106; 55.5%). Regular updating of the information in the register showed that 5.2% of patients are deceased and the majority (94.8%) is a subject to continuous monitoring as it has been reported for other European countries as well. With the establishment of the ExpC, the dynamics in the diagnosis and registration of patients with PID significantly intensified. For a period of 5 years (2016-2021) 101 patients were evaluated and registered in comparison with previous period - before ExpC establishment when only 89 patients were diagnosed. The most common pathology was humoral immune deficiency (85 patients; 44.5%). Ninety-six (50.3%) of the patients underwent genetic testing, and 66. 7% had genetically confirmed diagnosis. Three of the variants have not been reported in population databases. Following genetic investigation confirmation of the initial phenotypic diagnosis was achieved in 82.8% of cases and change in the diagnosis - in 17%. Sixty-two patients were on regular replacement or specific therapy, and the rest received symptomatic and supportive treatment. In summary, we present the first epidemiological report of PIDs in Bulgaria, based on the National PID register. Data on the clinical, phenotypic and genetic characteristics of PID patients provided important information about the nature of primary immunodeficiency diseases in our country.